Effect of various metal oxides phases present in CuMnOx catalyst for selective CO oxidation. (June 2018) - Dey, Subhashish; Dhal, Ganesh Chandra; Mohan, Devendra; Prasad, Ram
Graphical abstract: Abstract: Hopcalite (CuMnOx) is a highly efficient catalyst for low temperature oxidation of Carbon monoxide (CO). As synthesized by Co-precipitation method, it shows the high activity for CO oxidation. The coordination between CuO and MnOx in CuMnOx catalyst improves the catalytic activity for CO oxidation. In this research work, we investigate the individual catalytic activity of CuO and MnOx and compare with the multiphase CuMnOx catalyst. The performance of multiphase catalysts CuO and MnO2 were numerous times higher as compared to single phase CuMnOx. The activity order of catalysts for CO oxidation was as follows: CuMnOx > MnOx > CuOx. The success of CuMnOx catalyst has prompted a great deal of research work into each component and nature of active sites. In CuMnOx catalyst, the MnOx acts as an oxygen donor and CuO acts as an oxygen acceptor. The presence of MnOx is possible to assist in the reduction of CuO, due to the coordination between CuO and MnOx . The calcination strategies of precursors highly affect the physicochemical and catalytic properties of the catalysts for CO oxidation. The reactive calcination (RC) conditions (4.5% CO in air) for prepared catalysts showed the best activity result for CO oxidation, as compared to the traditional method of calcination.